2018
DOI: 10.33546/bnj.452
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Education Intervention on Knowledge of Cervical Cancer Prevention Among Women in Bahorok’s Village, North Sumatra Indonesia

Abstract: Background: Cervical cancer is the second cancer disease that attacks women in the world, and it ranked the first in developing countries. It is expected that woman’s knowledge about cervical cancer will prevent the incidence among them.  Objective: To examine the effect of health education on the knowledge level of women about cervical cancer prevention.Methods: This was a pre-experimental study with one group pretest posttest at Bahorok’s Village, North Sumatra, Indonesia on April to May 2016. There were 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
4
0
3
Order By: Relevance
“…25 The previous research by Simanullang showed there was significant effect of health education on women's knowledge about cervical cancer at Bahorok village, North Sumatra. 6 To conclude this study, there was a significant effect of health education in increasing the level of women's awareness about pap smear's ability to detect and prevent cervical cancer, thereby reducing women's mortality. Suggestions for further research are required to represent a greater number of respondents and a wider region.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…25 The previous research by Simanullang showed there was significant effect of health education on women's knowledge about cervical cancer at Bahorok village, North Sumatra. 6 To conclude this study, there was a significant effect of health education in increasing the level of women's awareness about pap smear's ability to detect and prevent cervical cancer, thereby reducing women's mortality. Suggestions for further research are required to represent a greater number of respondents and a wider region.…”
Section: Discussionmentioning
confidence: 86%
“…5 Public knowledge about the pap smear's early detection and prevention of cervical cancer is still low and health promotion is required to improve their familiarity about the disease. 6 Therefore, the socialization of pap smear's early detection and prevention of cervical cancer is very necessary to change the behavior of the women in maintaining their health, especially their reproductive organs. Cervical cancer can mostly be prevented, namely, by avoiding risk factors, screening or early detection, and treating with human papillomavirus (HPV) vaccination to reduce mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Kanker adalah suatu penyakit yang dialami oleh semua manusia di dunia terutama pada wanita, yaitu kanker serviks (Simanullang et al 2020;Simanullang, S Ilyas, et al 2021;Simanullang and Sitopu 2020) dan kanker payudara dan dari penelitian terdahulu menemukan bahwa salah satu factor ini disebabkan oleh rendahnya tingkat pengetahuan wanita untuk pencegahan kanker (Clarke et al 2018;Simanullang 2018;Simanullang, Syafruddin Ilyas, et al 2021). Kanker payudara adalah salah satu penyakit dan bahkan sampai sekarang tidak diketahui apa penyebabnya (Afiyanti, Wardani, and Martha 2019;Haakensen and D. 2018).…”
Section: Pendahuluanunclassified
“…Di Indonesia, prevalensi penyakit kanker cukup tinggi. Berdasarkan data Riset Kesehatan Dasar (Riskesdas) tahun 2013, prevalensi tumor/kanker di Indonesia adalah 1.4 per 1000 penduduk, atau sekitar 347.000 orang kanker pada perempuan tertinggi adalah kanker payudara dan kanker leher rahim (serviks) (Simanullang, 2018). Di Kota Medan sampai dengan tahun 2016 tercatat 2.493 orang yang telah diperiksa IVA dan SADANIS, dengan hasil temuan 110 positif kasus kanker (Wahidin et al 2012).…”
Section: Pendahuluanunclassified
“…Siskawati dan Simanullang (2022), bahwa ada pengaruh edukasi terhadap kepatuhan pasien chronic kidney disease dalam pembatasan intake cairan di Ruang Haemodialisa Di Rumah Sakit Aminah Tangerang (Siskawati & Rostime, 2022) dan Simanullang, 2018 menyatakan ada hubungan edukasi dengan pengetahuan ibu tentang karies gigi pada anak di Sekolah Dasar Helvetia Medan (Simanullang, 2018b). Selanjutnya dikatakan oleh Simanullang (2018) bahwa ada pengaruh edukasi terhadap tingkat pengetahuan wanita tentang kanker serviks di Bahorok (Simanullang, 2018a) dan papsmear pencegahan dini kanker serviks (Simanullang & Sitopu, 2020).…”
Section: Tingkat Pengetahuan Tentang Manfaat Edukasi Terhadap Penurua...unclassified